Motheater - Codega, Linda H. (Erewhon Books, an imprint of Kensington Publishing Corp., 2025)
"In this nuanced queer fantasy set amid the Appalachian Mountains in Virginia, the last witch of the Ridge must choose sides in a clash between industry and nature. After her best friend dies in a coal mine, Benethea "Bennie" Mattox sacrifices her job, her relationship, and her reputation to uncover what's killing miners on Kire Mountain. When she finds a half-drowned white woman in a dirty mine slough, Bennie takes her in because it's right--but also because she hopes this odd, magnetic stranger can lead her to the proof she needs. Instead, she brings more questions. The woman called Motheater can't remember her true name, or how she ended up inside the mountain. She knows only that she's a witch of Appalachia, bound to tor and holler, possum and snake, with power in her hands and Scripture on her tongue. But the mystery of her fate, her doomed quest to keep industry off Kire Mountain, and the promises she bent and broke have followed her a century and half into the future. And now, the choices Motheater and Bennie make together could change the face of the town itself." --